2007
DOI: 10.1021/es0700294
|View full text |Cite
|
Sign up to set email alerts
|

Time Trends of Methylmercury in Walleye in Northern Wisconsin:  A Hierarchical Bayesian Analysis

Abstract: Methylmercury data from walleye fillets collected by multiple agencies from northern Wisconsin lakes from 1982 to 2005 were examined for regional time trends. Hierarchical Bayesian methods were used to model dependencies and provide probability statements for parameters pertaining to individual lakes and the region as a whole. A missing data mechanism allowed the sex of the fish to be included as a predictor since the sexes grow at different rates. A slight regional decrease in methylmercury of 0.60% annually … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
14
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 25 publications
5
14
1
Order By: Relevance
“…Hg concentrations in northern pike and walleye from Minnesota declined by an average of 11% between 1990 and 2000, or~1% per year (MPCA 2007). Madsen and Stern (2007) found walleyes (skin-on and skin-off fillets) from northern Wisconsin decreased 0.6%/year over 1982-2005 using hierarchical Bayesian methods. In a study of common loons in northern Wisconsin, Fevold et al (2003) estimated that adult loon blood Hg levels decreased by 4.2% per year, while loon chick blood Hg decreased by 4.9% per year.…”
Section: Discussionmentioning
confidence: 99%
“…Hg concentrations in northern pike and walleye from Minnesota declined by an average of 11% between 1990 and 2000, or~1% per year (MPCA 2007). Madsen and Stern (2007) found walleyes (skin-on and skin-off fillets) from northern Wisconsin decreased 0.6%/year over 1982-2005 using hierarchical Bayesian methods. In a study of common loons in northern Wisconsin, Fevold et al (2003) estimated that adult loon blood Hg levels decreased by 4.2% per year, while loon chick blood Hg decreased by 4.9% per year.…”
Section: Discussionmentioning
confidence: 99%
“…For example, within-lake concentrations of mercury in these piscivorous fish decreased in 35% but increased in 60% of lakes. Concentrations of mercury in walleye in northern Wisconsin have also decreased by about 0.5% annually between 1982 and 2005, remained relative constant in the middle latitude lakes of the state, but have increased approximately 0.8% annually in southern Wisconsin (Madsen and Stern 2007;Rasmussen et al 2007). Bhavsar et al (2010) reported that, since 1990, mercury in walleye has declined in Lake Superior (0.18-0.20 lg g -1 wet weight per decade) and Lake Huron (0.05-0.07 lg g -1 wet weight per decade), remained unchanged in Lake Ontario, and has increased in Lake Erie (0.036 lg g -1 wet weight per decade).…”
Section: Estimated Mercury Concentration In Standard-size Fishmentioning
confidence: 99%
“…Trend analysis of walleye (Sander vitreus) in Wisconsin lakes between 1982 and 2005 has shown an annual percent change (APC) of 0.5 to 0.6% in northern Wisconsin and an upward trend of 0.8% APC in southern Wisconsin (Madsen and Stern 2007;Rasmussen et al 2007). Over the same period in Minnesota (1982Minnesota ( -2006, the overall trend in walleye and northern pike (Esox lucius) was the same as northern Wisconsin, but a better fitting piecewise linear regression model indicated a steeper decline of 4.7% per year from 1982 to 1992, followed by an increase of 1.4% per year for 1992-2006 (Monson 2009).…”
Section: Introductionmentioning
confidence: 99%